2010
DOI: 10.1177/0269881110379289
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and smoking status in antipsychotic-treated patients

Abstract: Studies investigating the relationship between cigarette smoking and prolactin secretion in the general population have yielded inconsistent results. Many antipsychotic drugs increase prolactin secretion, but there are no published studies that have investigated the relationship between smoking and prolactinaemia in antipsychotic-treated patients. We obtained prolactin levels from 228 antipsychotic-treated patients in secondary care mental health services and investigated the relationship between prolactinaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Others have also reported hyperprolactinemia in newly diagnosed, antipsychotic-naïve patients (Aston et al, 2010; Lee and Kim, 2006; Segal et al, 2007), although the patient and control subjects were less extensively matched on potentially confounding variables such as smoking (Mackin et al, 2011). Our findings suggest that hyperprolactinemia is not due to stress associated with the onset of psychosis, as cortisol levels were similar in both groups, but due to a pre-existing vulnerability.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Others have also reported hyperprolactinemia in newly diagnosed, antipsychotic-naïve patients (Aston et al, 2010; Lee and Kim, 2006; Segal et al, 2007), although the patient and control subjects were less extensively matched on potentially confounding variables such as smoking (Mackin et al, 2011). Our findings suggest that hyperprolactinemia is not due to stress associated with the onset of psychosis, as cortisol levels were similar in both groups, but due to a pre-existing vulnerability.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Finally, serum PRL rises after exercise, meals, sexual intercourse, minor surgical procedures, general anesthesia, acute myocardial infarction, an epileptic seizure (including after electroconvulsive therapy) and other forms of acute stress [5, 6, 55, 61]. Interestingly, several recent studies reported that current and ex-cigarette smokers on antipsychotic medication have significantly lower mean PRL levels, compared with nonsmokers [6365]. It is known that cigarette smoking is a potent inducer of the hepatic cytochrome P450 1A2 enzyme, and smoking may therefore result in a reduction of serum concentration of some antipsychotic drugs, which may, in turn, result in lower PRL levels [63].…”
Section: Diagnosis Of Hyperprolactinemia (Hprl)mentioning
confidence: 99%
“…Interestingly, several recent studies reported that current and ex-cigarette smokers on antipsychotic medication have significantly lower mean PRL levels, compared with nonsmokers [6365]. It is known that cigarette smoking is a potent inducer of the hepatic cytochrome P450 1A2 enzyme, and smoking may therefore result in a reduction of serum concentration of some antipsychotic drugs, which may, in turn, result in lower PRL levels [63]. However, further studies are needed to elucidate the underlying mechanism(s) [63, 64].…”
Section: Diagnosis Of Hyperprolactinemia (Hprl)mentioning
confidence: 99%
See 1 more Smart Citation
“…When evaluating hyperprolactinaemia it is also critical to understand the incidence or prevalence of hyperprolactinaemia from the patient perspective as opposed to a mean level from a cohort. Recent data are now tending to more commonly include both variables (Mackin et al, 2011) whereas in our 2008 review of this topic we reported that though 60% of studies reporting prolactin data included some degree of categorical analysis, this was seen mainly in the naturalistic studies (88%) rather than the randomised controlled trials (42%) (Bushe et al, 2008). …”
Section: Measurement Of Prolactin and Definition Of Hyperprolactinaemiamentioning
confidence: 91%